Identification of the Feasibility Level of Eco Tourism Attraction 4A’s Component of Lagundi Anyer Beach - Farida Farida; Joseph Aldo Irawan; Tanjung Prasetyo (Jurnal Toursci, 2026)
Background. The economy of Indonesia's coastal areas is greatly supported by marine tourism. Many destination development projects lack a systematic feasibility study of their attractiveness component. Purpose. This study aims to analyze the feasibility level of Component 4A as a tourist attraction of Lagundi Anyer Beach using the Analysis of Object Operations and Natural Tourism Attractions (ADO-ODTWA) method. Method. The research used a quantitative descriptive approach with purposive sampling, involving 30 tourists. Data analysis was used to weight ADO-ODTWA from the 4A components (Attraction, Amenities, Accessibility, and Ancillary). Conclusion. The result is that Lagundi Anyer Beach is very feasible to be developed or of high value, with the support of aspects of attractiveness, accessibility, and facilities that are categorized as high as well as aspects of Implementation. Institutions that need to be improved.